Hoisting-Loop in Bacterial Multidrug Exporter AcrB Is a Highly Flexible Hinge That Enables the Large Motion of the Subdomains - Zwama, Martijn; Hayashi, Katsuhiko; Sakurai, Keisuke; Nakashima, Ryosuke; Kitagawa, Kimie; Nishino, Kunihiko; Yamaguchi, Akihito (Frontiers in Microbiology, 2017)
The overexpression of RND-type exporters is one of the main causes of multidrug resistance in Gram-negative pathogens. In RND transporters, such as Escherichia coli’s main efflux pump AcrB, drug efflux occurs in the porter domain, while protons flow through the transmembrane domain: remote conformational coupling. At the border of a transmembrane helix (TM8) and subdomain PC2, there is a loop which makes a hoisting movement by a random-coil-to-α-helix change, and opens and closes a drug channel entrance. This loop is supposed to play a key role in the allosteric conformational coupling between the transmembrane and porter domain. Here we show the results of a series of flexibility loop-mutants of AcrB. We determined the crystal structure of a three amino acid truncated loop mutant, which is still a functional transporter, and show that the short α-helix between Cβ15 and the loop unwinds to a random coil in the access and binding monomers and in the extrusion monomer it becomes a partially stretched coil-to-helix change. The loop has undergone compensatory conformational changes and still facilitates the opening and closing of the channel. In addition, more flexible mutated loops (proline mutated and significantly elongated) can still function during export. The flexibility in this region is however limited, as an even more truncated mutant (six amino acid deletion) becomes mostly inactive. We found that the hoisting-loop is a highly flexible hinge that enables the conformational energy transmission passively.